The use of an ultrasonic cement removal device in revision hip and knee arthroplasty—A matched case‐control study - Marco Haertlé; Lars‐René Tücking; Alexander Derksen; Magnus Reulbach; Eike Jakubowitz; Henning Windhagen (Journal of Experimental Orthopaedics, 2025)
Abstract Purpose The objective of this case series was to investigate the effect of ultrasound‐guided cement removal devices on operating time and patient safety in the revision of cemented knee and hip arthroplasties. Methods A total of 11 cases were examined in which ultrasound‐guided cement extraction was utilised for implant removal. The primary endpoint of the study was the duration of the surgery. Additionally, the cohort was analysed for the occurrence of intraoperative fractures or postoperative ossification. Postoperative laboratory dynamics of haemoglobin and C‐reactive protein levels were also investigated. A matched group of 11 patients who underwent revision arthroplasty using conventional techniques to remove bone cement served as the reference group. Results Ultrasound‐guided removal of cement from the medullary canal was associated with a significantly longer operation time (187.19 min ± 54.4 vs. 121.91 min ± 43.5, (p = 0.0026). Furthermore, there was a significant decrease in haemoglobin drop relative to baseline haemoglobin levels when ultrasound‐guided tools were employed for cement removal (2.36 g/dL ± 1.9 vs. 4.54 g/dL ± 1.9, p = 0.0015). Moreover, an intraoperative fracture complication of the femoral shaft was observed when the cement was removed using an ultrasonic cement stripper. Conclusion A comparison between the two groups reveals a significant increase in surgical duration when cement removal was performed using ultrasound‐guided technique. Simultaneously, the use of an ultrasound‐assisted system for cement removal did not mitigate the risk of intraoperative bone perforation. Based on the data presented in this study, the authors cannot conclude that the use of ultrasound‐guided devices for the removal of cement residues from the medullary canal during revision surgery is superior to conventional techniques. Level of Evidence Level IV.